Supporting new graduate physiotherapists in their first year of private practice with a structured professional development program; a qualitative study. (February 2022) - Chipchase, L.; Papinniemi, A.; Dafny, H.; Levy, T.; Evans, K.
Abstract: Background: The transition from physiotherapy student to working in private practice has been identified as challenging. However, very little is known about whether structured professional development programs impact on this transition. Objectives: To describe new graduates' perceptions of a structured professional development program, termed the Recent Graduate Program (RGP), designed to support their transition into physiotherapy private practice. Design: Qualitative analysis of data from a one-year longitudinal mixed methods study. Method: A total of 72 interviews were conducted over a one-year period with 20 new graduates from 19 private practices within one publicly listed allied health organisation. Semi-structured interviews were conducted before commencing work and at three, nine and 12 months. Interviews were recorded and transcribed verbatim prior to a conventional content analysis that aimed to acquire direct information from new graduates without imposing preconceived categories or theoretical perspectives. Findings: New graduates reported that the RGP supported their growth as a practitioner and facilitated their learning, particularly when complemented by the experiential learning from client interactions. The RGP met their expectations with the formal education program and regular mentoring sessions highly valued. Informal support from peers and senior clinicians, while not part of the RGP, was also perceived to facilitate their growth and confidence as a physiotherapist. Conclusions: This study demonstrates that the provision of a structured transition program by a private practice employer was perceived by new graduates to facilitate their learning, confidence and self-efficacy. The RGP provides a useful model by which other practices may support new graduates. Highlights: Research supporting transition to physiotherapy private practice is limited. A year long recent graduate program (RGP) was developed and evaluated. The RGP met the expectations of new graduates. The RGP supported professional growth, learning, confidence and self-efficacy. Informal support and mentoring were highly valued by new graduates.